2017
DOI: 10.1590/1980-5497201700020004
|View full text |Cite
|
Sign up to set email alerts
|

Feminicídios na cidade de Porto Alegre: Quantos são? Quem são?

Abstract: ABSTRACT:Objective: To quantify and typify the feminicides occurred in the city of Porto Alegre from 2006 to 2010. Methods: Cross-sectional study that examines the sociodemographic characteristics of victims and perpetrators and the circumstances of feminicides obtained in police investigations of women murdered in the city of Porto Alegre. Statistical analyses were performed using the SPSS software, version 20.0, with the χ 2 test; p <0.05 was considered as significant. Results: Of the 89 surveys analyzed, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 7 publications
1
15
0
18
Order By: Relevance
“…Median age of femicide victims was relatively low and much lower than victims of other violent deaths, corroborating a study in Porto Alegre 27 and differing from findings in other countries 23,26 . In Italy, for example, more than half of the victims were over 45 years of age 23 .…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Median age of femicide victims was relatively low and much lower than victims of other violent deaths, corroborating a study in Porto Alegre 27 and differing from findings in other countries 23,26 . In Italy, for example, more than half of the victims were over 45 years of age 23 .…”
Section: Discussionsupporting
confidence: 73%
“…Saúde Pública 2019; 35(8):e00230418 occurred in public. This result is largely expected, since studies on femicide 27,41 and on deadly assaults perpetrated by intimate partners show that the domicile is the most frequent site of fatal assault 42 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…These findings are in agreement with what other studies have reported regarding the murder of women in retaliation against their partners or relatives, and the violent death of women and children in areas affected by drug trafficking. (19,21,32) The second category with the highest number of homicides was femicide, since 11 (15.7%) were perpetrated by the victim's intimate partner, besides in 8 cases (72.7%) the victims' age ranged between 13 and 15 years old at the time of their deaths, which reveals and early occurrence of this type of crime. In this sense, in 2013 the National Institute of Legal Medicine and Forensic Sciences of Colombia expressed its concerns regarding the increase in the number of femicides of minors.…”
Section: Discussionmentioning
confidence: 99%